An Examination of Travel Effects on Performance Outcomes in Major League Soccer - Evan Gilbert; Jess Dixon; Todd Loughead (Journal of Applied Sports Management, 2020)
The home advantage (HA) is a well-documented phenomenon across team sports, including association football (soccer). The effects of travel play a role in the HA, although the nature in which travel affects performance is still unknown. Match data from Major League Soccer (MLS) were used to investigate the role that crowd factors, travel, and team quality play in the HA. The results demonstrated the negative effect of a connecting flight by the visiting team on match outcomes. Also, in comparison to drawn matches, home team wins and losses increased when traveling east.
Keywords: Football; Health; Home advantage; Manageament; Soccer